A critical analysis of Vacca, A., Aru, F., and Ollesch, G. (2017). Short‐term impact of coppice management on soil in a Quercus ilex L. Stand in Sardinia. Land Degradation & Development, 28(2), 553–565. (6th August 2019) - Giadrossich, Filippo; Guastini, Enrico
Abstract: Inappropriate forest management degrades the quality of soil resources. Soil erosion, for instance, leads to decreased soil fertility and landscape quality. Coppice‐wood management includes risk factors for soil erosion due to the partial and temporary lack of soil cover, and this review highlights the importance of considering both an adequate methodology and objective interpretation of findings. This critical review was carried out due to the substantial deficiencies in the research design and methodology, analysis and interpretation of data, and conclusions in the paper that are not supported by their findings. In this paper, we provide a different interpretation of their data, which reveals absence of substantial risk of soil erosion, even in the short period after coppicing when the soil is most exposed. We aim to provide a clearer context for readers about the impact of coppice management in Quercus ilex stands in the south of Sardinia.